Tiếp <=> x+yxy(√1−xx+√−(y−1)y)+((x−y)(x+y)x2y2(√x2+1x−√y2+1y)=0 <=> x+yxy(1√1−xx+√−(y+1)y+x−yxy(√x2+1x2+√y2+1y2))=0 <=> x=-yThày vào pt (1) : 12x^{2}-19x+5=−x√6(x+1) <=> {12x2−19x+5≤0(12x2−19x+5)2=6x2(x+1) <=> {...........≤0(2x−1)(3x−5)(24x2−25x+5)=0.......... Đến bước này bạn tự giải nha ĐA : (x;y)=(1/2;-1/2) hoặc (x;y)= ( 25+√14548;(−25+√14548)
Tiếp <=>
x+yxy(√1−xx+√−(y−1)y)+((x−y)(x+y)x2y2(√x2+1x−√y2+1y)=0 <=>
x+yxy(1√1−xx+√−(y+1)y+x−yxy(√x2+1x2+√y2+1y2))=0 <=> x=-yThày vào pt (1) :
$12x^{2}-19x+5
$=
−x√6(x+1) <=>
{12x2−19x+5≤0(12x2−19x+5)2=6x2(x+1) <=>
{...........≤0(2x−1)(3x−5)(24x2−25x+5)=0.......... Đến bước này bạn tự giải nha ĐA : (x;y)=(1/2;-1/2) hoặc (x;y)= (
25+√14548;(−25+√14548)